Code-Switching in Indonesian Novel Divortiare by Ika Natassa - Khansa Nailah Hanin Andyti; Qanitah Masykuroh (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The purpose of this study is to classify, identify, and analyse the various forms of code-switching that are present in Ika Natassa's Divortiare. The study focuses on how the novel's narrative style, emotional expression, and characterization are influenced by the alternation between Indonesian and English. Methodology: A qualitative text analysis design is used in this study. The novel's bilingual Indonesian and English utterances make up the primary data. Documentation technique, such as repeated reading, underlining, and methodical classification of instances of code-switching, were used to collect data. The analysis adheres to the qualitative methods of data condensation, data display, and conclusion drawing described by Miles, Huberman, and Saldaña (2014). The primary analytical tools used were Poplack's (1980) structural framework and Gumperz's (1982) functional model, which were backed by pertinent sociolinguistic and bilingualism theories. Results: According to the results, Divortiare demonstrates three different forms of code-switching: tag switching, inter-sentential switching, and intra-sentential switching. Specifically, the novel's code-switching serves a number of communicative purposes, such as message qualification, interjection, repetition, and personalization. The analysis shows that English insertions function as stylistic devices that reflect contemporary urban Indonesian culture, heighten emotion, and create character identity in addition to acting as linguistic alternations. Applications/Originality/Value: By illustrating how structural types and communicative functions interact to create character voice and narrative meaning, this study advances literary linguistics. The results show how bilingual expression functions as a stylistic tool in modern Indonesian fiction, enhancing affective tone, influencing interpersonal relationships, and portraying bilingual speakers in social contexts.